Diseño de un producto de turismo comunitario para fomentar el desarrollo local en el cantón Bolívar provincia de Manabí - Ganchozo Basurto, María Auxiliadora (2015)
The tourism community product was held in communities such as Cabello, San Miguel de Sarampion, Chapuli, La Esperanza, Primera Piedra, Julian, located in Bolivar Canton: Several researcher methodologies contributed to the development of this Community product, such as deductive, inductive, surveys and some scientific methods. After analyzing the current tourism situation in which are the towns metioned above, it was possible to identify the attractions and resources in the area, which allowed to take into account the resources that will be included in the research proposal. Through the application of surveys it was easy to identify, the tourism market, visitor profile, supply, demand potential, and promotion strategies that will be used for feasibility and uptake of the product. The tourism community product is looking to promote the tourism development in communities Cabello, Sarampión, Chapuli, Primera Piedra, Julian, and Esperanza, these six villages are the main beneficiares, increasing the interest in the Bolivar canton. According to the results provided in this investigation it was concluded that the canton community Bolivar has a high potential for tourism in rural areas specifically in the afore mentioned communities, which emphasizes their natural and cultural resources, and working together with institutions of Bolivar canton, will consolidate and promote the development of the area, benefiting both directly, communities and Bolivar canton.